Students’ and Teachers’ Perspectives on EFL Textbook For Senior High School Students - Lina Herliana; Soenarjati Djajanegara; Mamik Suendarti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2020)
The purpose of this study is to evaluate the effectiveness of an English textbook “Bahasa Inggris SMA/MA/SMK/MAK Kelas X” from the perspectives of students and teachers. The textbook was prepared by the Indonesian Ministry of National Education for the 10th-grade students and used by some teachers during the 2018-2019 academic year. The evaluation of the concern for the textbook is carried out at the macro level based on eleven parameters. Data was obtained through student questionnaires administered to 94 students and through interviews with four teachers. The data were analyzed and grouped according to 11 criteria used in this study for the evaluation of the particular textbook. The results revealed that both teachers and students felt negative about some of the characteristics of the textbook. It was found that the reading passages needed to be simplified in terms of vocabulary load and that the grammar needed to be presented in detail. The majority of students indicated that the level of the textbook was not appropriate for the particular age group. The teachers pointed out that the tasks and activities were not organized from easy to difficult stages. Also, the listening activities were not supported by audio recordings that should have been included in the textbook. Moreover, the students expected the book to include multiple-choice exercises. It implies that some aspects of the textbook need to be revised, and the audio recordings must be included to support the listening activities. On the other hand, one of the strengths of the textbook was that the activities in the textbook involved opportunities that encourage students’ creativity, interest, and curiosity.Keywords: EFL textbook, textbook evaluation, macro evaluation